Longitudinal analysis of pupillometry according to type of pharmacotherapy in Parkinson’s disease patients - Olga Bartošová; Petr Dušek; Martin Šíma; Daniel Stránský; Jan Hlaváč; Evžen Růžička; Karel Šonka; Ondřej Slanař (Scientific Reports)
Abstract The aim of this study was to evaluate the effect of different types of pharmacotherapy on pupillometric parameters in PD patients. Dopamine was shown to induce mydriasis by excitation of alpha-adrenergic receptors at the dilator pupillae muscle. Pupil diameter may thus serve as an indirect measure of peripheral dopaminergic activity. A total of 63 PD patients were treated with different types of dopaminergic pharmacotherapy. Pupil examination was performed before the first application of dopaminergic pharmacotherapy and then after one year of treatment in the OFF state and in the ON state. There were significant differences in pupillometric parameters obtained at baseline and at year 1 OFF and ON. The pupillometry did not differ among type of used pharmacotherapy in most pupillometric parameters. Two-way ANOVA confirmed the significant effect of visit in the pupillometric parameters MAX and MIN, but did not confirm the significant effect treatment between groups of patients with L-DOPA pharmacotherapy and with dopamine agonist. Linear regression analysis showed significant dose-response relationships between the most pupillometric parameters and L-DOPA equivalent doses in the patients treated with L-DOPA and dopamine agonist. In conclusion, this analysis does not confirm a differential pupillary response according to type of pharmacotherapy in PD patients.